Exploring Environmental Damage in Novel The Color Purple by Alice Walker and Bekisar Merah by Ahmad Tohari: A Literature Ecocritics Review - Olga A. Rorintulus; Maissy Jearmita Manuas; Ignatius J. C Tuerah (English Education Postgraduate Program, Universitas Negeri Manado, 2022)
This study aims to discuss what environmental damage is discussed in the novels The Color Purple by Alice Walker and Bekisar Merah by Ahmad Tohari In this study using a qualitative method as the method data collection is done by analyzing the dialogues in the novel and then writing it down and researching it The use of supporting sources is also applied in this study For further research it is suggested to put more emphasis on what environmental damage occurred in the novel and compared it with environmental damage in the real world Comparisons like this are very interesting to study but due to the lack of available sources it is requested to conduct further research < em>< p>